RETROPHARYNGEAL ABSCESS: A HIDDEN COMPLICATION OF PERFORATED THORACIC ESOPHAGEAL CANCER - Geanina Bandol; B.M. Cobzeanu; O.D. Palade; Liliana Moisii; Florentina Severin; Nicoleta Anton; Emilia Patrascanu; Laura Rîșcanu; A.Andoni; M.D. Cobzeanu (Romanian Society of Oral Rehabilitation, 2024)
BACKGROUND. Deep neck infections have significant morbidity and mortality. The most common complications are mediastinitis and sepsis. Acute mediastinitis continues to be a serious condition with a high mortality rate. The common primary sources of infection are of odontogenic etiology, pharyngo-laryngeal infections, cancers and iatrogenic. Most esophageal perforations are iatrogenic (50-75%) and most occur during endoscopic procedures. MATERIAL AND METHODS. We present the case of a 60-year-old patient who developed a deep neck infection two weeks after undergoing a biopsy for a mass located in the thoracic segment of the esophagus. RESULTS. The therapeutic management consisted of placing a tracheostomy tube, performing a lateral cervical incision to permit drainage of the abscess, lavage, and drainage of the superior mediastinum along with aggressive antibiotherapy. The postoperative evolution was favorable, with the CT scan showing no remaining colections and blood samples almost returning to normal values. CONCLUSIONS. Clinical evaluation, appropriate imaging, and aggressive active management are vital to successful outcomes for deep neck infections (DNIs). The origins of DNIs are usually evident from clinical and radiological examination. However, efforts should be made to identify the source of infection and this should be treated at the same time or electively.